2009
DOI: 10.3989/scimar.2009.73n4785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fatty acid profile of muscle neutral lipids and phospholipids of up-river anadromous sea lamprey (<i>Petromyzon marinus</i> L.) from three Portuguese river basins

Abstract: SummarY: Composition of fatty acid profile of muscle neutral lipids (nl) and phospholipids (Pl) of sea lamprey that enter the Portuguese rivers minho, tagus and Guadiana during their non-trophic spawning migration was analysed. the fatty acid profile exhibited differences in the percentage among nl and Pl and between river basins. Similarities were found in the fatty acid profile of nl. monounsaturated fatty acids (muFa) were the most representative, followed by saturated fatty acids (SFa) and finally by polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
6
7
0
Order By: Relevance
“…The predominance of DHA (C22:6w3) relative to EPA (C20:5w3) in the sea lamprey´s fillets has been reported previously (Pinela et al, 2009;Lança et al, 2013) and verified in several species of fish (Ozogul et al, 2007;2011;Prato and Biandolino, 2012). Furthermore, for both river basin individuals, there was a negative correlation between DHA levels and total lipid content, which is common in some fish species (Tocher, 2003;Afonso, 2009).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The predominance of DHA (C22:6w3) relative to EPA (C20:5w3) in the sea lamprey´s fillets has been reported previously (Pinela et al, 2009;Lança et al, 2013) and verified in several species of fish (Ozogul et al, 2007;2011;Prato and Biandolino, 2012). Furthermore, for both river basin individuals, there was a negative correlation between DHA levels and total lipid content, which is common in some fish species (Tocher, 2003;Afonso, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…The fatty acid profile of fillets was like that of several fish species because most fish primarily accumulate lipid reserves as SFA and MUFA (Tocher, 2003;Pinela et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The predominance of DHA (C22:6w3) relative to EPA (C20:5w3) in the sea lamprey´s fillets has been reported previously (Pinela et al, 2009;Lança et al, 2013) and verified in several species of fish (Ozogul et al, 2007;2011;Prato and Biandolino, 2012). Furthermore, for both river basin individuals, there was a negative correlation between DHA levels and total lipid content, which is common in some fish species (Tocher, 2003;Afonso, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…The fatty acid profile of fillets was like that of several fish species because most fish primarily accumulate lipid reserves as SFA and MUFA (Tocher, 2003;Pinela et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In fish caught in nature, in TAG mostly monoenes, then saturated followed by PUFA are found (Henderson & Tocher, 1987). Based on this, it has been found that fish species accumulate mainly SFA and MUFA as stored lipids (Pinela et al, 2009). The reason for the high rate of monoenes in triacylglycerol is that among the components in this group, the ratio of 18:1-9 is higher.…”
Section: Maymentioning
confidence: 93%